2007
DOI: 10.1248/cpb.55.1744
|View full text |Cite
|
Sign up to set email alerts
|

Abietane Lactones and Iridoids from Goldfussia yunnanensis

Abstract: The genus Goldfussia NEES (Acanthaceae) with more than 30 species is distributed in India, Malaysia and China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Larval hosts of J. lemonias include native plant species in the genera Barleria, Goldfussia, Hygrophila, Nelsonia, Phyla, and Sida (Chou, 1994;Igarishi and Fukada, 1997;Kunte, 2000;Ekpo and Etim, 2009), all of which have been reported to contain iridoid glycoside secondary compounds (Jensen and Neilsen, 1985;Jensen et al, 1988;Yu et al, 2007;Jaiswal et al, 2014;Kim et al, 2015). Three additional plant genera, Lepidagathis, Corchorus, and Cannabis, are also known larval hosts for J. lemonias but are not yet known to contain iridoid glycosides (Igarishi and Fukada, 1997;Kunte, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Larval hosts of J. lemonias include native plant species in the genera Barleria, Goldfussia, Hygrophila, Nelsonia, Phyla, and Sida (Chou, 1994;Igarishi and Fukada, 1997;Kunte, 2000;Ekpo and Etim, 2009), all of which have been reported to contain iridoid glycoside secondary compounds (Jensen and Neilsen, 1985;Jensen et al, 1988;Yu et al, 2007;Jaiswal et al, 2014;Kim et al, 2015). Three additional plant genera, Lepidagathis, Corchorus, and Cannabis, are also known larval hosts for J. lemonias but are not yet known to contain iridoid glycosides (Igarishi and Fukada, 1997;Kunte, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other studied Chloranthus species that are rich in sesquiterpenoids, the current research shows that ent -abietane-type diterpenoids are the major secondary metabolites of C. sessilifolius . A literature survey showed that ent -abietanoids have been previously obtained only from the following genera: Ceriops (family: Rhizophoraceae), Suregada (family: Euphorbiaceae), Euphorbia (family: Euphorbiaceae), Isodon (family: Labiatae), Goldfussia (family: Acanthaceae), Doellingeria , and Solidago (family: Compositae) . Our findings add to the diversity and complexity of ent -abietanes and their natural origins.…”
Section: Resultsmentioning
confidence: 99%